2019
DOI: 10.1002/ange.201907466
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐Switchable HCl Transport Enabled by Lipid Headgroup–Transporter Interactions

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…37 In more recent studies, Gale and co-workers reported unexpected behavior of several high-affinity anion transporters, such as 28. 39,40 They were active in H + /Cl À symport and Cl À /NO 3 À exchange but failed to facilitate the uniport of H + or Cl À ions. This has been attributed to the strong interaction between anion transporters and the phosphate headgroup of lipids, which inhibits the transmembrane diffusion of free transporters suppressing the uniport process but not the exchange process, which does not require free-transporter diffusion.…”
Section: Llmentioning
confidence: 99%
See 2 more Smart Citations
“…37 In more recent studies, Gale and co-workers reported unexpected behavior of several high-affinity anion transporters, such as 28. 39,40 They were active in H + /Cl À symport and Cl À /NO 3 À exchange but failed to facilitate the uniport of H + or Cl À ions. This has been attributed to the strong interaction between anion transporters and the phosphate headgroup of lipids, which inhibits the transmembrane diffusion of free transporters suppressing the uniport process but not the exchange process, which does not require free-transporter diffusion.…”
Section: Llmentioning
confidence: 99%
“…This mechanism also leads to interesting voltage-dependent transport properties. 39 Gale and Howe also reported a prototype biomimetic transmembrane pumping system in which externally added fatty acids were used as fuels to generate a pH gradient and pump Cl À ions out of liposomes against their concentration gradient. 41 Matile and co-workers have pioneered the research of using non-covalent interactions other than hydrogen bonds to facilitate transmembrane anion transport.…”
Section: Llmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, a proton gradient can be dissipated to pump chloride ions and generate a chloride gradient. The proton gradient generated by the fatty acid pump (Figure 31) was combined with chloride anionophores [91] to pump chloride across a membrane driven by the addition of fatty acids [44b,c] …”
Section: Information Ratchetsmentioning
confidence: 99%
“… Gale's 2019 fatty‐acid‐fuelled anion pump [44b,c] . Chloride anionophores symport chloride and protons across a membrane.…”
Section: Information Ratchetsmentioning
confidence: 99%